(untitled) (Canadian Medical Education Journal, 2025)
Implication Statement Encounter-based teaching is vital to medical education, however feedback can be difficult to obtain. We developed and evaluated a web-based application (app) called “myTeachingEvaluation” (myTE.orgTM). Thirty-four academic clinical teachers participated in a needs assessment; 47% reported ≥50% of their teaching was undocumented. We invited participants to pilot myTE.orgTM over eight weeks. Thirteen faculty piloted the app and 62% of them (8/13) reported the app enabled documentation of ≥50% of previously undocumented teaching. myTE.orgTM app creates opportunities for efficient and timely feedback.